Ultrahigh Resolution Pixelated Top‐Emitting Quantum‐Dot Light‐Emitting Diodes Enabled by Color‐Converting Cavities. Issue 1 (28th November 2021) - Chen, Lianna; Qin, Zhiyuan; Chen, Shuming
Abstract: Realizing pixelated quantum‐dot light‐emitting diodes for high‐resolution displays remains a challenging task because of the difficulty of fine patterning the quantum‐dots. In this study, instead of patterning the quantum‐dots, the color‐converting cavities for realizing high‐resolution pixelated emission are developed. By defining the thicknesses of the transparent electrodes (phase tuning layers) through a photolithographic process, the resultant cavities can selectively convert the unpatterned quantum‐dot white emission as saturated red, green, and blue emission with a brightness of 22170, 51930, and 3064 cd m −2 at 5.5 V, respectively. The developed method enables the realization of ultrahigh density red, green, and blue emission for a display with a resolution of ≈1700 pixel‐per‐inch and a color gamut of 111% National Television System Committee; together with the advantages of quantum‐dot patterning‐free, color‐filter‐free and high brightness, the demonstrated architecture could find potential applications in various displays ranging from cell phone to emerging virtual reality and augmented reality displays. Abstract : The photopatternable color‐converting cavity is developed to realize ultrahigh resolution pixelated red, green, and blue quantum‐dot (QD) light‐emitting diode arrays. By simply photopatterning the IZO phase tuning layers, the cavity can selectively convert the unpatterned QD white emission as color‐saturated and color‐stable red, green, and blue emission with a resolution of ≈1700 pixel‐per‐inch and a color gamut of 111% national television system committee.